STUDY OF THE MECHANISM OF ALDOL CONDENSATION OF ACETALDEHYDE IN ACIDIC AND BASIC CATALYTIC SYSTEMS (E Global Congress, 2025)
To study the mechanism of the aldol condensation of acetaldehyde, 2MgO/SiO2 and 2ZrO2*FeO*ZnO/SiO2 catalysts with a mass fraction of MgO and ZrO2 of 2% were prepared, which had high catalytic activity and productivity and were selected for the process.